A presença de Nicolas Bourbaki na Universidade de São Paulo - Pires, Rute da Cunha (2006)
This work aimed to establish the importance of the French group called Nicolas Bourbaki in the development of the mathematical research and teaching instruction at the Faculdade de Filosofia, Ciências e Letras da Universidade de São Paulo. The reasons for the presence, for intermittent periods, from 1945 to 1966, of some of the most important mathematicians of the Bourbaki group at the college math department is discussed and how the perception and assimilation of the bourbakist structure of the mathematics has been transmitted and re-read by the academic community of the University of São Paulo at the time. Documents and bibliographical material were acquired in order to constitute, characterized and built the research goal. Bourbaki presence at São Paulo University was mainly due to two factors, the II world war and the bounds between professors from USP and those from other parts of the world that have been here around the time of its foundation. A great number of courses and conferences was given by the group, while here in Brazil, and through those we can raise parameters that point out to the influence of the Bourbaki perspective on the mathematics production at the university